Mejora el rendimiento de los estudiantes utilizando la multimedia con interacción alumno profesor - Pilozo Solano, Richard (2011)
During their academic journey, students do not develop skills that are necessary for their personal and professional life as the oral and written communication, learn independently, teamwork, critical thinking, among others, as they are inured to a traditional class, where students are passive recipients of information. The purpose of this study was to improve the academic performance of students in the Dynamics unit using Problem Based Learning with different levels of complexity in the drafting stage. We used a sample of 180 students enrolled in an introductory course in physics at a university and were assigned to four intact groups. The Group A and B were treated PBL with the same scenery but different complexity, in Group C and D, were developed based on traditional class and sceneries before mentioned. We measured the homogeneity of the groups and finally found the academic performance using a knowledge test, the result was analyzed with F-ANOVA statistical tool with significance level of 0.05. This study tested the hypothesis that students who were applied PBL or a higher level of complexity in the drafting stage, have better academic performance than students who were not subject to anything.